An Empirical Analysis of Informational Relevance of Product QR Codes in Nepal - Prajapati, Gopi (NPRC Journal of Multidisciplinary Research, 2026)
Background: QR code has been an important part of retail products. From food and beverages to electronics, we can find these square-shaped patterns printed on the product itself or packages. While this QR technology has been widely adopted, it is uncertain whether they successfully fulfill their purpose of providing product-specific relevant information or not.Methods: A sample of 150 products across five categories (food, beverages, cosmetics, electronics, and household products) was collected from retail stores in Kathmandu Valley. I have used a standardized smartphone (iPhone 14 Pro) to scan the QR codes on the products. The outcomes of scans were classified into four different categories: Relevant, Partially relevant, Irrelevant and Failed. Data were then analyzed using descriptive statistics to determine percentage distribution over the categories.Results: The study revealed that highest percentage (63%) of QR codes directed to irrelevant marketing or social media pages. Only 16% of QR codes provided product specific information.Conclusion: Majority of QR codes fail to deliver product relevant information which creates a gap between consumer expectation and information delivery. This study suggests recommendations for brands, policy makers and future research directions based on empirical findings.Novelty: This research contributes to the literature on information quality and consumer access to information by providing an empirical analysis on QR code informational relevance. These shifts focus from consumer perception and adoption to content auditing of QR codes.